2020
DOI: 10.1111/exd.14167
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative analysis of advanced glycation end products in atopic dermatitis—Possible culprit for the comorbidities?

Abstract: Advanced glycation end products (AGEs) interact with the membrane‐bound receptor for AGEs (RAGE), consequently amplifying the inflammatory response. Soluble receptor for AGE (sRAGE) and endogenous secretory RAGE (esRAGE) act as decoys for AGE and competitively sequester RAGE ligands, thereby serving a cytoprotective role. Our objective was to investigate AGE expression and their receptors in the serum and skin of patients with atopic dermatitis (AD). In this case‐control study, the levels of AGE, sRAGE and esR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A previous study found that urinary pentosidine, an AGE formed by sequential glycation and oxidation, tends to be higher in AD patients with acute exacerbation ( Tsukahara et al, 2003 ). Correspondingly, the level of AGEs in corneocytes from AD patients is increasing along with lesion severity ( Hong et al, 2020 ). Additionally, an increasing expression of receptor for AGEs (RAGE) is observed in AD-like mouse models, which results in the release of pro-inflammatory cytokines ( Dumitriu et al, 2005 ; Karuppagounder et al, 2015 ; Wang et al, 2018 ).…”
Section: Involvement Of Post-translational Modifications In Adsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that urinary pentosidine, an AGE formed by sequential glycation and oxidation, tends to be higher in AD patients with acute exacerbation ( Tsukahara et al, 2003 ). Correspondingly, the level of AGEs in corneocytes from AD patients is increasing along with lesion severity ( Hong et al, 2020 ). Additionally, an increasing expression of receptor for AGEs (RAGE) is observed in AD-like mouse models, which results in the release of pro-inflammatory cytokines ( Dumitriu et al, 2005 ; Karuppagounder et al, 2015 ; Wang et al, 2018 ).…”
Section: Involvement Of Post-translational Modifications In Adsmentioning
confidence: 99%
“…We emphasized that aberrant PTMs could trigger complex cascades of multi-cellular and multi-factorial pathways in AD pathophysiology, and the diagnostic and prognostic significance of PTMs should however be mentioned. Currently, dermal AGEs and urinary pentosidine have been used as biomarkers for early detection and prognosis estimation in AD ( Tsukahara et al, 2003 ; Hong et al, 2020 ). With the introduction of skin autofluorescence in AGEs measurement, it raises the possibility of non-invasive tools in assessing both the disease severity and the comorbidity risks in the future ( Ying et al, 2021 ).…”
Section: Potential Clues For Atopic Dermatitis Diagnosis and Treatmentmentioning
confidence: 99%
“…AGE level is greatly elevated during ageing and in poorly controlled diabetes, cardiovascular diseases and atherosclerosis 40,42 . Recent studies, including one published in EXD, have found that AGE levels are also increased in the skin and blood of patients with PSO or AD 41,43 . AGEs may activate membrane receptors of epithelial cells and immune cells, promoting the production of proinflammatory cytokines and reactive oxygen species and the activation of metalloproteases 41 .…”
Section: Disease Aetiologymentioning
confidence: 99%
“…However, RNA expression profiling of uninvolved and lesion skin from psoriasis patients showed decreased expression of Glo1 [60]. Hong et al reported that the skin of patients with atopic dermatitis (AD) has a higher expression of AGEs in corneocytes than in normal healthy controls, and the accumulation of dermal AGEs in AD increases oxidative stress, causing skin inflammation [61]. AD is a chronic inflammation of the skin characterized by pruritus and eczema.…”
Section: Glyoxalase In Miscellaneous Skin Abnormalitiesmentioning
confidence: 99%